The effect of “terroir” products on territorial attractiveness and development. Case of the Souss Massa region - Bouchra EL BAKKOURI; Ghizlane AMAJID; Malika SOUAF; Youssef ELWAZANI (Revue Marocaine de l'Entrepreneuriat, de l'Innovation et du Management, 2018)
Terroir products are becoming a real economic booster because consumers attach more importance to their characteristics, their cultural identity and appearance. These products can contribute to the protection of cultural heritage, to socio-cultural development and to poverty-reduction in rural areas (FAO 2009). The question we raise through this article regards the effects of these terroir products on attractiveness and development of their territories. To explore these effects, we offer a critical study of secondary data (literature, reports, statistics ...) about the relationship between terroir products and the attractiveness and development of their territories. We chose the region of Souss Massa to study two Moroccan terroir products as application the Souss Massa region and study two Moroccan terroir products: Argan oil and Saffron spice . we decided to compare these two chosen products are with another french terroir product which is the Laguiole cheese so that we can to make draw conclusions about their effects on the attractiveness and the development of their territories. As a resulttrhe study reveals that, indeed, the terroir products have positive effects on both the development and the attractiveness of their territories that is why they should be more and more valued.